Compatibility of Whole Wheat-Based Composite Flour in the Development of Functional Foods - Amani Weerarathna; Matara Arahchige Jagath Wansapala (Food Technology and Biotechnology)
Over the last decades, eating habits have shifted towards convenient foods with shorter preparation times due to people’s busy lifestyles and higher living standards. Rapid changes in dietary patterns and lifestyles with the industrialization and globalisation have led to the escalating incidence of chronic diseases, which has paved the way to greater interest in dietary changes regarding nutritional status and health benefits. Composite flour is a combination of wheat and non-wheat flours or exclusively non-wheat flour with improved nutritional value, therapeutic properties and functional characteristics. The application of composite flours in the food industry is an important milestone that maximises the use of indigenous crops while optimising the product quality, nutritional value, organoleptic properties and consumer acceptance. This paper provides a comprehensive overview of the suitability and compatibility of alternative composite flours in the food industry with regard to the existing formulations. Furthermore, the suitability of composite flours in food products in terms of nutritive and therapeutic value is emphasised. It was found that food products with higher nutritional and therapeutic value and acceptable sensory properties can be formulated by blending different non-wheat flour sources with wheat flour at different ratios. Composite flours have the potential to reduce the risk of non-communicable diseases, particularly type 2 diabetes, cardiovascular disease and cancer. It can be concluded that the use of composite flours in the food industry is a trending approach due to their numerous benefits.